First Report of the Italian Registry on Immune-Mediated Congenital Heart Block (Lu.Ne Registry) - Fredi, Micaela; Andreoli, Laura; Bacco, Beatrice; Bertero, Tiziana; Bortoluzzi, Alessandra; Breda, Silvia; Cappa, Veronica; Ceccarelli, Fulvia; Cimaz, Rolando; De Vita, Salvatore; Di Poi, Emma; Elefante, Elena; et al. (Frontiers in Cardiovascular Medicine, 2019)
Objective: Neonatal Lupus (NL) is a rare syndrome caused by placental transfer of maternal anti-SSA/Ro and anti-La/SSB autoantibodies to the fetus. The rarity of this condition requires the establishment of multidisciplinary registries in order to improve our knowledge. Method: Inclusion criteria in this retrospective study were the maternal confirmed positivity for anti-SSA/Ro and/or anti-SSB/La antibodies, and the presence of II or III degree congenital heart block (CHB) in utero or neonatal period (up to 30 days after birth). Result: Eighty-nine cases of CHB were observed in 85 women with 88 pregnancies that occurred between 1969-2017. CHB was mostly detected in utero (84 cases, 94.2%), while 5 cases were observed in the neonatal period. A permanent pacemaker was implanted in 51 of 73 children born alive (69.8), whereas global mortality rate was 25.8% (23 cases): 16 in utero, 5 perinatal and 2 during childhood. By univariate analysis, factors associated with fetal death were pleural effusion (p=0.005, OR>100; CI95% 2.88->100 and hydrops (p=0.003, OR=14.09; CI95% 2.01-122). Fluorinated steroids (FS) were administered in 71.4% pregnancies, and its use was not associated with better survival. Some centers treated all cases with fluorinated steroids and some centers did not treat any case. CHB was initially incomplete in 24 fetuses, and of them five cases of II degree block reverted to a lower degree block after treatments. Recurrence rate in subsequent pregnancies was 17.6% (3 out of 17). A prophylactic treatment was introduced in 10 of these 16 subsequent (58.8%) pregnancies, mostly with FS or high dose intravenous immunoglobulins. Conclusion: this is the first report from the Italian Registry of neonatal lupus/CHB. The live birth rate was nearly 80%, with nearly two thirds of the children requiring the implantation of a pacemaker. The management of fetuses diagnosed with CHB was heterogeneous across Italian Centers. The registry at present is mainly rheumatological, but involvement of pediatric cardiologists and gynecologists is planned.